2018
DOI: 10.1186/s12864-018-5189-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of skin color microRNAs in Koi carp (Cyprinus carpio L.) by Illumina sequencing

Abstract: BackgroundMicroRNAs (miRNAs) are endogenous, small (21–25 nucleotide), non-coding RNAs that play important roles in numerous biological processes. Koi carp exhibit diverse color patterns, making it an ideal subject for studying the genetics of pigmentation. However, the influence of miRNAs on skin color regulation and variation in Koi carp is poorly understood.ResultsHerein, we performed small RNA (sRNA) analysis of the three main skin colors in Koi carp by Illumina sequencing. The results revealed 330, 397, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…Animals' coloration and their pattern is an important model to excavate the genetic mechanisms that determine phenotype (Joanna et al, 2010). In this study, we mainly focused on the miR-206 functional studies based on previous small RNA sequencing results (Luo et al, 2018). Firstly, we analyzed its temporal and spatial expression pattern to gain insight into the functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals' coloration and their pattern is an important model to excavate the genetic mechanisms that determine phenotype (Joanna et al, 2010). In this study, we mainly focused on the miR-206 functional studies based on previous small RNA sequencing results (Luo et al, 2018). Firstly, we analyzed its temporal and spatial expression pattern to gain insight into the functions.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes, such as tyrosinase-related protein-1 (Tyrp1) and dopachrome tautomerase (Dct or Tyrp2), primarily regulate the eumelanin pathway (Braasch et al, 2009). Interestingly, we also identified some important miRNAs and mRNAs on black, white, and red skin of koi carp, which involved in the cAMP signaling, melanogenesis, and tyrosine metabolism pathway through Illumina sequencing (Luo et al, 2018;Luo et al, 2019). Therefore, it is necessary to further excavate the specific relationship between the coding and non-coding RNAs, e.g.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our previous study, we identified important miRNAs (e.g. miR-196a , miR-125b , miR-200b and miR-206 ) that influence pigmentation and differentiation in the three main skin colors [23]. Despite an abundance of literature on tissue-specific expression patterns and functions of mRNAs and miRNAs in fish, evidence for tissue-restricted expression of lncRNAs is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we performed small RNA sequencing (sRNA-Seq) on three skin colors (black, white and red) in Koi carp using Illumina sequencing. We screened 164 differentially expressed miRNAs and identified several key miRNAs related to pigment regulation including miR-196a , miR-200b , miR-125b and miR-202 [23]. In the present study, we conducted a high-throughput sequencing strategy to screen expression of lncRNAs and mRNAs in these three skin colors.…”
Section: Introductionmentioning
confidence: 99%